If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + A = 3 + -1X + Y Solving 5 + A = 3 + -1X + Y Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + A = 3 + -1X + -5 + Y Combine like terms: 5 + -5 = 0 0 + A = 3 + -1X + -5 + Y A = 3 + -1X + -5 + Y Reorder the terms: A = 3 + -5 + -1X + Y Combine like terms: 3 + -5 = -2 A = -2 + -1X + Y Simplifying A = -2 + -1X + Y
| 8(4+3)+2(7-5)/5(7-3)2 | | 100=9+8+14+x | | 3(a-5)= | | A=3-X+Y | | A=3+-1X+1Y | | (2x+7)+(-5x-14)= | | (6x+8)+(-7x-19)= | | 4x+5=87-2x | | 14xy-21yz= | | 4x+3y=30 | | 2y-7=y+9 | | (x+4)(x-1)=24 | | 2(x+5)-6=16 | | -15=x+(-16) | | X-Y+A=3 | | X-Y+Z=3 | | x-2/12=5/6 | | -1+y/8=15 | | 4x+8y+20= | | 3x^3-7.5x^2-32=0 | | -3+m/9=10 | | -10=-2+1/2d | | 158-3x=24x+20 | | 6-7x=51-42x | | X-Y+C=3 | | 2x^2-1=9 | | 76-2x=10x-2x | | 12x-4=4x-3 | | 3y+4=7-4y | | 2(2x+7)+3(x+2)=5(x-1)-1 | | 6x-8=2x+32 | | 1+8x=22x+x |